2020
DOI: 10.1515/cclm-2020-0975
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three fully-automated SARS-CoV-2 antibody assays

Abstract: ObjectivesSerological assays for detection of SARS-CoV-2 antibodies are increasingly used during the COVID-19 pandemic caused by the SARS-Coronavirus-2. Here we evaluated the analytical and clinical performance of three commercially available SARS-CoV-2 antibody assays.MethodsA total of 186 samples from 58 patients with PCR-confirmed COVID-19 infection were measured using SARS-CoV-2 antibody assays by Siemens Healthineers, Roche Diagnostics and Euroimmun. Additionally, 123 control samples, including samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 25 publications
6
18
0
1
Order By: Relevance
“…The specificities would remain high even if the two presumed false-negative RT-PCR patient samples were included in the analysis. There has been little literature regarding the Siemens assay, although recent reports indicate excellent specificity, 13 , 20-22 which our findings further support with a wide array of samples. The specificities of the DiaSorin and EUROIMMUN assays are similar to, or modestly lower, than other evaluations, 2-4 , 8 -11,13-17,19,21,36 although some of the studies reporting better performance had very small number of samples or nonchallenging cross-reactivity panels.…”
Section: Discussionsupporting
confidence: 86%
“…The specificities would remain high even if the two presumed false-negative RT-PCR patient samples were included in the analysis. There has been little literature regarding the Siemens assay, although recent reports indicate excellent specificity, 13 , 20-22 which our findings further support with a wide array of samples. The specificities of the DiaSorin and EUROIMMUN assays are similar to, or modestly lower, than other evaluations, 2-4 , 8 -11,13-17,19,21,36 although some of the studies reporting better performance had very small number of samples or nonchallenging cross-reactivity panels.…”
Section: Discussionsupporting
confidence: 86%
“…For instance, we obtained 85% and 83% sensitivities for the Roche and Abbott assays in the ≥15 days period while the companies claimed 100% sensitivity at the same time frame. Similarly to our findings, other studies reported smaller Se values varying from 73 to 89% and 82 to 92% for the Roche and Abbott assays respectively (19)(20)(21). Clinical performance characteristic variations between serological studies are not unusual and are highly dependant on the patient cohort used for evaluation.…”
Section: Downloaded Fromsupporting
confidence: 88%
“…Regarding the rapid antibody detection devices, we obtained relatively good Se and Sp values which were lower than those claimed by the manufacturers but similar to published studies (19,26). Downloaded from so far that could be bypassed by several proposed strategies.…”
Section: Downloaded Fromsupporting
confidence: 88%
“…In addition, as the N protein could interact with many host proteins during the infection process and cause a robust humoral immune response after infection, the divergent charge distribution surfaces could be critical to identify specific interacting cellular proteins and develop specific immune‐based rapid diagnostic test (Burbelo et al , ; Ni et al , ). Besides the serological assays for detection of SARS‐CoV‐2 antibodies (Hörber et al , ), the rapid detection of viral antigens based on specific antibodies can provide essential information for disease monitoring (Che et al , ). Therefore, to develop high‐affinity and specific anti‐N antibodies would be critical to enhance the rapid molecular diagnosis for COVID‐19.…”
Section: Discussionmentioning
confidence: 99%